Extracellular matrix pretreatment improves morphology and functionality in Müller glial cells in a retinal degeneration mouse model - Vallese, Harmonie Agostina (2022)
Müller glial cells (MGC) are retina specialized cells, which promote photoreceptors (PHR) survival. We demonstrated that they are stem cells, whose regenerative potential and lamellipodia are decreased in the retinal degeneration mouse (rd1), compared to the wild type (wt). This suggests that the extracellular matrix (ECM) could be al- tered in rd1, affecting rd1 MGC morphology and functionality, and interfering with substrate adhesion and lamellipodia extensions, hence leading to an excessive number of neurons interacting with MGC. The aim of this work was to study rd1 ECM protein expres- sion and localization, and determine whether ECM pretreatment could restore the rd1 MGC morphology and functionality. Using mixed neuro-glial cultures obtained from postnatal 2 days rd1 and wt mice retinas, we analyzed by immunocytochemistry, osteonectin and fibronectin (FN) expression and focal adhesions (FAs) stained with paxillin. Also, rd1 mixed neuro-glial cultures were seeded on culture dishes previously treated or not with ECM-enriched condi- tioned medium (ECM-CM) obtained from Schwanomma (RN22) cell line, to analyze rd1 MGC morphology, FAs, proliferation and PHR survival (using BrdU and DAPI, respectively). Our results showed a decrease in osteonectin expression and both number and length of FAs along with an increase in fibrillary FN expression in rd1 MGC, when compared to the wt condition. Also, FAs showed cortical lo- cations and mature shape in rd1 compared to the wt. Noteworthy, ECM-CM pretreatment restored rd1 FAs and MGC lamellipodia ex- tensions, hence decreasing the ratio in number of neurons growing on MGC. This ECM pretreatment, also promoted rd1 MGC prolifer- ation and decreased PHR death. As a whole, these results suggest that rd1 neuro-glial cultures present alterations in EMC protein syn- thesis and/or secretion, and that ECM supplementation improves MGC morphology and functionality.